2018
DOI: 10.1249/jes.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise’s Ability to Reverse Cancer-Induced Anabolic Resistance

Abstract: Skeletal muscle has the dynamic capability to modulate protein turnover in response to anabolic stimuli, such as feeding and contraction. We propose that anabolic resistance, the suppressed ability to induce protein synthesis, is central to cancer-induced muscle wasting. Furthermore, we propose that resistance exercise training has the potential to attenuate or treat cancer-induced anabolic resistance through improvements in oxidative metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 50 publications
(201 reference statements)
2
45
0
1
Order By: Relevance
“…These same muscles when interrogated for proteins implied in AKT pathway indicated no AKT activation, because AKT, 4EBP-1, mTOR and S6K were no more phosphorylated upon running (Figure S7). This can be explained by “anabolic resistance”, typical of cachexia [41]. Only the expression of musclin was partially recovered in gastrocnemius from trained C26-bearing mice (Figure 6f).…”
Section: Resultsmentioning
confidence: 99%
“…These same muscles when interrogated for proteins implied in AKT pathway indicated no AKT activation, because AKT, 4EBP-1, mTOR and S6K were no more phosphorylated upon running (Figure S7). This can be explained by “anabolic resistance”, typical of cachexia [41]. Only the expression of musclin was partially recovered in gastrocnemius from trained C26-bearing mice (Figure 6f).…”
Section: Resultsmentioning
confidence: 99%
“…Anabolic resistance, the inability for anabolic stimuli to induce muscle protein synthesis, has been investigated as a driver of age-related sarcopenia (61, 62) and disuse atrophy (31). While anabolic resistance has been reported in cancer patients (56, 63), further investigation is needed to determine the mechanistic underpinnings of this resistance, and to identify the upstream mediators responsible for suppressed anabolic signaling in cachectic muscle (64). Protein degradation is also a tightly regulated process mediated by ubiquitin-proteasomal activation and proteasomal-autophagy-lysosomal pathways (65).…”
Section: Cancer-induced Disruption To Skeletal Muscle and Sexual Dimorpmentioning
confidence: 99%
“…Resistance exercise is a non-pharmacological intervention that can modulate muscle fiber composition, protein turnover, oxidative phosphorylation, and hormones, and it has been extensively reviewed (64, 99, 100). Resistance exercise can benefit the cancer patient’s quality of life and physical function (11, 99102).…”
Section: Potential Therapeutic Interventionsmentioning
confidence: 99%
“…For decades now, endurance and resistance exercise have been proposed as promising therapies as they broadly impact chronic inflammation, metabolic homeostasis, and muscle protein turnover ( Al-Majid and McCarthy, 2001 ; Montalvo et al, 2018 ). There are barriers to exercise as a therapeutic for cancer cachexia as it is unlikely that a level of exercise to induce muscle mass can be performed by patients with debilitating conditions like cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated that TNF-α plays a key role in cancer and DOX-induced skeletal muscle dysfunction ( Hardin et al, 2008 ; Gilliam et al, 2009 , 2011 ). While disrupted protein turnover has been a central regulator of cancer-induced cachexia ( White et al, 2013 ; Montalvo et al, 2018 ; Counts et al, 2020 ), there is little evidence to suggest chemotherapy impacts muscle in this same way.…”
Section: Cancer and Chemotherapy-induced Cachexia Overviewmentioning
confidence: 99%